Efforts to Improve Student Learning Outcome in Bahasa Indonesia on Map Material through Problem Based Learning Model - Rosmiati, Cucu; Carlian, Yayan (Al-Aulad: Journal of Islamic Primary Education, 2023)
This research is motivated by the low learning outcomes of students in Class II of MI Nurul Falah Kota Cimahi, which is caused by the Indonesian language learning process still being teacher-centered, with teachers following the habit of directly presenting the material and then evaluating students through exercises. The aim of this study is to improve students' learning outcomes in the Indonesian language subject, specifically in the topic of "denah," using the problem-based learning model in Class II of MI Nurul Falah Kota Cimahi. This research is a Classroom Action Research focusing on actions to improve students' learning outcomes in the Indonesian language subject, specifically in the topic of "denah," using the Problem-Based Learning model in Class II of MI Nurul Falah Kota Cimahi. The results of the action research conducted by the author in two cycles resulted in an increase in student learning mastery. In the pre-cycle, 10 students passed with a percentage of 38% and an average score of 59.04%. In Cycle I, this increased to 16 students with a percentage of 62% and an average score of 69.40%, and in Cycle II, it further increased to 26 students with a percentage of 100% and an average score of 80.00%. This proves that the implementation of the problem-based learning model in Indonesian language learning, specifically in the "denah" topic, can improve students' engagement and learning outcomes.